The Logistics Factors that Affect the Academic Achievement of Elementary School Students in the Kingdom of Saudi Arabia (Applied Statistical Study) (Global Journal of Sciences, 2025)
This study aimed to examine the impact of logistical services on the academic  achievement of primary school students using Exploratory Factor Analysis (EFA) and  Stepwise Discriminant Analysis (DA). The EFA revealed five factors that explained  64.1% of the total variance: School Environment, Distance Between School and Home,  Logistics Factors 1, Level of Education According to School Location, and Logistics  Factors 2. These factors were extracted based on eigenvalues greater than 1 and were  rotated using the Varimax method. Subsequently, four of these components were  sequentially entered into the discriminant model through stepwise analysis: Level of  Education According to School Location, Logistics Factors 1, Logistics Factors 2, and  School Environment. Results indicated that Level of Education by Location was the  most significant discriminator (Wilks’ Lambda = .338, F = 3420.828, p < .001),  followed by logistical and environmental factors. The final model achieved a Wilks’  Lambda of .203. The standardized canonical discriminant function coefficients showed  that the Level of Education According to School Location had the most decisive  influence on the first discriminant function (1.055). As results indicate:  • School location significantly impacts academic achievement, whether a school is  located in an urban or rural area. • Improving logistical services, such as school transportation and delivering the  textbook early, as the delay of these factors affects student achievement negatively. • Attention to the school environment, including lighting, ventilation, and  recreational facilities, positively affects students' academic achievement. • The study recommends conducting future studies to investigate the remaining  variables using alternative statistical methods.
Keywords: Exploratory factor; analysis; Discriminant analysis Logistical factors; Academic achievement